Inventory of Plant Types of The Arecaceae Family in Campus I UIN Sunan Gunung Djati Bandung - Nursyafira Asma Humairah; Nursyifa Firda Prasetyanti; Ateng Supriyatna (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
The Arecaceae family is a palm plant that is widely used as an ornamental plant. Indonesia is one of the centers of high diversity of Arecaceae species. This family is called a multipurpose plant because it has various benefits for human life such as a source of food, oil producer, medicine, handicraft and household materials, ornamental plants and environmental conservation plants. The purpose of this research was to inventory the types of plants belonging to the Arecaceae family. The research was conducted at Campus I UIN Sunan Gunung Djati Bandung which was divided into two locations using the observation method. The results showed that there were several types of Arecaceae plants in the area of UIN Sunan Gunung Djati Campus I, namely Adonidia merrillii, Cyrtostachys renda, Dypsis lutescens.